THE INFLUENCE OF THE FAMILY HOPE PROGRAM (PKH) AGAINST POVERTY ALLEVIATION IN ISLAMIC ECONOMIC PERSPECTIVE - Winda Jayanti; Rina Novianty (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This study discusses the Family Hope Program (PKH) and its effect on poverty alleviation in Waetuwo Village, Tanete Riattang Timur District, Bone Regency. The Harapan Family Program is one of the assistance programs for the poor, especially the fulfillment of basic education and health needs for children from poor families, which is a government program to overcome poverty problems. This research was conducted with the aim of knowing the effect of the Family Hope Program (PKH) on poverty alleviation from an Islamic economic perspective.The results showed that there was a positive and significant effect of the Family Hope Program on poverty alleviation in Waetuwo Village, although it showed a relatively low correlation or relationship value. This is supported by the results of descriptive analysis which shows that the Family Hope Program in the short term can provide an income effect (the impact that occurs when changes in prices or income will increase) to RTSM through reducing the burden on household expenses so that it can break the poverty chain through efforts to increase access to education and health, which was 3.8% while 96.2% was influenced by other factors. Viewed from the perspective of Islamic Economics in alleviating poverty based on the Islamic Economic system which has the principle of social security and the realization of welfare (Falah), in its implementation the new Family of Hope Programis only limited to government social security to meet health and education needs for poor families, however To obtain welfare (Falah), the Family Hope Program cannot be said to be able to improve the welfare of the poor.Penelitian ini membahas tentang Program Keluarga Harapan (PKH) serta pengaruhnya terhadap Pengentasan Kemiskinan di Kelurahan Waetuwo Kecamatan Tanete Riattang Timur Kabupaten Bone. Program Keluarga Harapan merupakan salah satu program bantuan bagi masyarakat miskin khususnya pemenuhan kebutuhan dasar pendidikan dan kesehatan bagi anak-anak dari keluarga miskin yang merupakan program dari pemerintah untuk mengatasi masalah kemiskinan. Penelitian ini dilakukan dengan tujuan untuk mengetahui pengaruh Program Keluarga Harapan (PKH) terhadap Pengentasan Kemiskinan dari segi Perspektif Ekonomi Islam.Hasil penelitian menunjukkan bahwa terdapat pengaruh positif dan signifikan dari pengaruh Program Keluarga Harapan terhadap pengentasan kemiskinan di Kelurahan Waetuwo, meskipun menunjukkan nilai korelasi atau hubungan yang relatif rendah. Hal ini didukung dari hasil analisis deskriptif yang menunjukkan bahwa Program Keluarga Harapan dalam jangka pendek dapat memberikan income effect (dampak yang terjadi ketika adanya perubahan harga atau pendapatan akan meningkat) kepada RTSM melalui pengurangan beban pengeluaran Rumah Tangga sehingga dapat memutus mata rantai kemiskinan melalui upaya peningkatan akses terhadap pendidikan dan kesehatan, yakni sebesar 3,8% sedangkan 96,2% dipengaruhi oleh faktor lain. Dilihat dari segi pandangan Ekonomi Islam dalam mengentaskan kemiskinan berdasarkan pada sistem Ekonomi Islam yang memiliki prinsip yaitu adanya jaminan sosial serta terwujudnya kesejahteraan (Falah), dalam implementasinya Program Keluarga Harapan baru hanya sebatas jaminan sosial pemerintah untuk memenuhi kebutuhan kesehatan dan pendidikan bagi keluarga miskin, namun untuk memperoleh kesejahteraan (Falah) Program Keluarga Harapan belum bisa dikatakan dapat mensejahterakan masyarakat miskin.